Cannibalism in the Brown Marmorated Stink Bug Halyomorpha halys (Stål) - Giulia Papa; Ilaria Negri (Insects, 2020)
The phytophagous brown marmorated stink bug Halyomorpha halys (Stål) is known to exhibit cannibalistic behaviour towards eggs. Here, we provide evidence of cannibalism among overwintering H. halys adults. Since diapausing individuals have high physiological demands for surviving long periods under stressful conditions, including the risk of depletion of metabolic reserves and desiccation, we assumed that nutritional and water requirements can be met by intraspecific predation. The role of aggregative behaviour in promoting cannibalism is also discussed. Given its evolutionary advantage, this trait should be maintained over generations and may be more widespread than previously considered in species that display aggregative behaviour during adverse seasons.